2021
DOI: 10.3390/su13073600
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of Eucalyptus Camdulensis Biochar in the Batch Adsorption of Crystal Violet and Methylene Blue Dyes from Aqueous Solution

Abstract: Eucalyptus camdulensis biochar (Ec-bio) was used to adsorb crystal violet (CV) and methylene blue (MB) dyes, which was optimized and further evaluated using different isotherm and kinetic models. Microscopy and spectroscopy techniques showed the interactions of the dyes with the surface functional groups of the Ec-bio, resulting in the removal of the dyes from aqueous solution. Both dyes were immediately uptaken, with equilibrium reached in 60 min, with a higher sorption efficiency of CV compared to MB. Thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 53 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…Table 5 illustrates the maximum adsorption capacities of MB-dye and CV-dye onto various types of natural biochars [1,22,24,28,33,[59][60][61][62]. The results represented in this table shows that the fabricated T-BC have considerable adsorption capacities comparing with other published works.…”
Section: Comparison Of Maximum Adsorption Capacities With Different N...mentioning
confidence: 84%
See 1 more Smart Citation
“…Table 5 illustrates the maximum adsorption capacities of MB-dye and CV-dye onto various types of natural biochars [1,22,24,28,33,[59][60][61][62]. The results represented in this table shows that the fabricated T-BC have considerable adsorption capacities comparing with other published works.…”
Section: Comparison Of Maximum Adsorption Capacities With Different N...mentioning
confidence: 84%
“…Phosphoric acid and Zinc chloride are two of the most often used activating agents in chemical activation, aside from NaOH and KOH [20,21]. Therefore, many research studies have been published during the last couple of years investigating the use of biochar to adsorb dyes and in wastewater treatment processes [22][23][24][25][26][27][28][29][30][31][32][33]. CV and/or MB dyes were adsorbed from aqueous media by various types of biochar such as eucalyptus camaldulensis biochar (Ec-bio) [22], porous biochar [23], mesoporous seaweed biochar [24], castor biomass-based biochar [25], adsorbents from orange peel residues [26], biochar at different carbonization times [28], date palm fronds biochars [31], and rice husk-mediated magnetic biochar (RH-MBC) [33].…”
Section: Introductionmentioning
confidence: 99%
“…The K d value of Sr 0.7 Mn 0.3 Co 0.5 Fe 0.5 O 3Àd /CAg was higher in comparison to other adsorbents in the literature. 7,[35][36][37][38][39][40] It was found that the DB-perovskite/CAg hybrid leads to a higher K d than other adsorbents, suggesting higher retention and low mobility of CV and AY17 in an aqueous solution. The CV molecules have smaller sizes than AY17.…”
Section: Resultsmentioning
confidence: 99%
“…Eb was prepared as reported previously [ 31 ], using Ec waste obtained from local areas around the city of Riyadh, Kingdom of Saudi Arabia. The collected waste was washed rigorously and thoroughly dried in an open atmosphere, and then the oven-dried (at 80°C for 6 hours) product was crushed in a ball mill to obtain an average particle size of nearly 5.0 mm.…”
Section: Methodsmentioning
confidence: 99%